Kant’s Ethical Position and the Problem of Corruption in Nigeria - Uzoigwe, Elias Ifeanyi E.; Chukwuma-Offor, Amara Mary (GNOSI: An Interdisciplinary Journal of Human Theory and Praxis, 2021)
Kant’s Ethical Position and the Problem of Corruption in Nigeria is aimed at making evident the prevalent nature of corruption in Nigeria and suggests the possible means of tackling the cankerworm that has eaten deep into the fabrics of the nation, negatively affecting the development of the country in almost all spheres of human endeavour. There is an urgent need for eradication of this menace, or at least reduce it drastically. Efforts have been made without bearing many fruits because those efforts were not anchored on a particular philosophy. As a result, this work calls for the adoption of Immanuel Kant’s Ethical Position, especially his categorical imperative as a vibrant and working philosophy in a quest for the eradication of this misnomer. By so doing, a sense of duty, goodwill, moral law, justice and fairness should be embraced by all Nigerians as a way of tackling this hydra-headed monster called corruption in the nation. Some of the methods employed in this work include: analytic, historical, textual, and contextual. Word count: 167